The capacity of human memory: Is there any limit to human memory? - Ehsan Namaziandost; Meisam Ziafar (Journal of Research on English and Language Learning (J-REaLL), 2020)
There exist some estimates of the capacity of human memory. Recent studies have proven the fact that Long Term Memory is subject to constant reconfigurations mostly at lower levels of neural clusters. There is no consensus on one definition for the capacity of memory. As far as retrieval of items present in memory is not the concern, it is reasonable to refrain from putting limits on capacity of human memory; otherwise, one must accept a number game which renders no fixed definite final estimation. Recently such capacity is defined as the amount of interference created by the item which must remain active in the memory.